Biomarkers and Bioanalysis Overview - Claudia Fernandes Nunes, Ane (IntechOpen, 2021)
Diagnosis is the basis for appropriate medical assistance. From the bench to the bed, physicians from different areas use several techniques to obtain accurate diagnoses. This book discusses some of the most current approaches to diagnosis in a variety of medical specialties. This collection of translational studies provides interesting reviews on pharmacology, drug biomarkers, nephrology and renal physiology, biochemistry, and cellular and molecular biology.